2014
DOI: 10.1016/j.indcrop.2014.03.041
|View full text |Cite
|
Sign up to set email alerts
|

Potential of antioxidant extracts produced by aqueous processing of renewable resources for the formulation of cosmetics

Abstract: The performance of natural extracts obtained from underutilized and residual vegetal and macroalgal biomass processed with food-grade green solvents was compared with that of commercial antioxidants. Selected extracts were obtained from two terrestrial sources: winery byproducts concentrate (WBC) and chestnut burs hydrothermally fractionated extract (CBAE), and from two underutilized seaweeds: Sargassum muticum extracts, either extracted with ethanol (SmEE) or after alginate extraction and hydrothermal fractio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 83 publications
(54 citation statements)
references
References 32 publications
2
50
0
2
Order By: Relevance
“…Balboa et al (2014) have suggested that fucoxanthin may represent a major commercial product from S. muticum. Gammone et al (2015) have recently reviewed the effect of various carotenoids (including fucoxanthin) on human health, and in particular cardiovascular health; Maeda (2015) has reviewed the use of fucoxanthin for obesity and diabetes therapy; and Zorofchian Moghadamtousi et al (2014) have reviewed the anticancer and antitumor potential of fucoxanthin.…”
Section: Carotenoidsmentioning
confidence: 99%
“…Balboa et al (2014) have suggested that fucoxanthin may represent a major commercial product from S. muticum. Gammone et al (2015) have recently reviewed the effect of various carotenoids (including fucoxanthin) on human health, and in particular cardiovascular health; Maeda (2015) has reviewed the use of fucoxanthin for obesity and diabetes therapy; and Zorofchian Moghadamtousi et al (2014) have reviewed the anticancer and antitumor potential of fucoxanthin.…”
Section: Carotenoidsmentioning
confidence: 99%
“…A winery byproduct concentrate, containing more than 50% phenolics, useful for the formulation of cosmetic emulsions and oils, showed no irritation in an Episkin test [64,65]. Products containing 3%-10% grape extracts were nonirritant in a dermal irritation test in human skin [5].…”
Section: Safetymentioning
confidence: 99%
“…This potential use was also confirmed by the low release of IL-1a as endpoint of the irritation process (in the range of negative control), which is a highly active and proinflammatory cytokine playing a key role in inflammation, being produced by keratinocytes. IL-1a is a highly active and pleiotropic proinflammatory cytokine that play a key role in inflammation, being the biological mirror of skin irritation (Balboa et al, 2014). Keratinocytes produces IL-1a and IL-1� mRNA in vitro, but only IL-1a biological activity has been identified in keratinocytes cultures (Mizutani et al, 1991).…”
Section: Skin Irritability Testsmentioning
confidence: 99%
“…Balboa et al (2014) evaluated the in vitro antioxidants properties and the skin irritant effects of natural extracts obtained from under-utilized and residual vegetal and macroalgal biomass. Extracts did not affect the human reconstructed epidermis but the cell via-bility was lower than in this study.…”
Section: Skin Irritability Testsmentioning
confidence: 99%